VZHE-039, a novel antisickling agent that prevents erythrocyte sickling under both hypoxic and anoxic conditions - Abdulmalik, Osheiza (Sci Rep, 2020)
Sickle cell disease (SCD) results from a hemoglobin (Hb) mutation βGlu6 → βVal6 that changes normal Hb (HbA) into sickle Hb (HbS). Under hypoxia, HbS polymerizes into rigid fibers, causing red blood cells (RBCs) to sickle; leading to numerous adverse pathological effects. The RBC sickling is made worse by the low oxygen (O(2)) affinity of HbS, due to elevated intra-RBC concentrations of the natural Hb effector, 2,3-diphosphoglycerate. This has prompted the development of Hb modifiers, such as aromatic aldehydes, with the intent of increasing Hb affinity for O(2) with subsequent prevention of RBC sickling. One such molecule, Voxelotor was recently approved by U.S. FDA to treat SCD. Here we report results of a novel aromatic aldehyde, VZHE-039, that mimics both the O(2)-dependent and O(2)-independent antisickling properties of fetal hemoglobin. The latter mechanism of action—as elucidated through crystallographic and biological studies—is likely due to disruption of key intermolecular contacts necessary for stable HbS polymer formation. This dual antisickling mechanism, in addition to VZHE-039 metabolic stability, has translated into significantly enhanced and sustained pharmacologic activities. Finally, VZHE-039 showed no significant inhibition of several CYPs, demonstrated efficient RBC partitioning and high membrane permeability, and is not an efflux transporter (P-gp) substrate.